2013
DOI: 10.1002/jclp.21980
|View full text |Cite
|
Sign up to set email alerts
|

Helping Vulnerable Populations: A Comprehensive Review of the Treatment Outcome Literature on Substance Use Disorder and PTSD

Abstract: We review treatment studies for comorbid substance use disorder (SUD) and posttraumatic stress disorder (PTSD). Results show positive outcomes on multiple domains. Most models had more effect on PTSD than SUD, suggesting SUD is harder to treat. Seeking Safety (SS) is the most studied model. It shows positive outcomes, and is the only treatment outperforming a control on both PTSD and SUD. Partial-dose SS had more mixed results than the full dose. This first-generation of PTSD/SUD research addresses complex sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
165
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 29 publications
9
165
0
6
Order By: Relevance
“…Women with a history of trauma are particularly vulnerable to revictimization, sexual abuse, shame, and stigma (Najavits & Hien, 2013). Studies have overwhelmingly demonstrated women with a diagnosis of post-traumatic stress disorder (PTSD) have increased rates of substance abuse and co-morbid psychiatric disorders (Banducci, Hoffman, Lejuez, & Koenen, 2014;Cohen, Field, Campbell, & Hien, 2013;Hien et al, 2010).…”
Section: Screening and Brief Intervention For Adverse Childhood Expermentioning
confidence: 99%
“…Women with a history of trauma are particularly vulnerable to revictimization, sexual abuse, shame, and stigma (Najavits & Hien, 2013). Studies have overwhelmingly demonstrated women with a diagnosis of post-traumatic stress disorder (PTSD) have increased rates of substance abuse and co-morbid psychiatric disorders (Banducci, Hoffman, Lejuez, & Koenen, 2014;Cohen, Field, Campbell, & Hien, 2013;Hien et al, 2010).…”
Section: Screening and Brief Intervention For Adverse Childhood Expermentioning
confidence: 99%
“…Além disso, outros estudos observaram maior risco de suicídio nos grupos com histórico de consumo múltiplo de substâncias, sugerindo a importância da avaliação de transtornos associados à dependência [26][27][28][29][30] . A vulnerabilidade da população de dependentes quí-micos demanda tratamento especializado, que deve ser adequado às particularidades de cada caso, a depender da gravidade da dependência, da aceitação do paciente, da presença de comorbidades e do perfil sociodemográfico 31,32 . As formas de tratamento disponíveis vão desde o tratamento ambulatorial na atenção básica, nos Centros de Reabilitação Psicossocial e nos grupos de ajuda mútua, até a internação, seja ela voluntária ou involuntária, em hospitais gerais, hospitais psiquiátricos, clínicas especializadas e em comunidades terapêuticas 31,33 .…”
Section: Introductionunclassified
“…PTSD is known to influence treatment adherence rates, with higher levels of PTSS being predictive of both lower adherence to treatment, and lower treatment retention (Najavits & Hien, 2013;Kubiak, 2004) Furthermore, higher levels of PTSS predict substance use relapse (Norman, Take, Anderson, & Brown, 2007;Ford, Hawke, Alessi, Ledgerwood, & Petry, 2007). This influence on treatment and relapse makes PTSD prohibitive of successful SUD treatment, especially as time spent in treatment is one of the only known predictors of treatment success in drug and alcohol rehabilitation (Hubbard, Craddock, & Anderson, 2003).…”
Section: Treating Ptsd and Sud Concurrentlymentioning
confidence: 99%
“…In a review of comorbid PTSD and SUD treatment programs, Seeking Safety was deemed largely efficacious (Najavits & Hien, 2013). The authors note that Seeking Safety does not worsen symptoms of either SUD or PTSD, and in many instances the symptoms of both SUD and PTSD improve.…”
Section: Treating Ptsd and Sud Concurrentlymentioning
confidence: 99%
See 1 more Smart Citation